4. Analysis of Raw Material Control Using Economic Order Quantity (EOQ) Method In Suppressing Inventory Costs At UD. Sagga Lather Malang. - Malang, Sekolah Tinggi Ilmu Administrasi (STIA) (Ilmu Administrasi, 2019)
AbstractThis study aims to determine the quantity or quantity of economic orders(EOQ), safety stock, point of re-ordering, and the total cost of raw materialsinventory of skin on UD. Sagga Leather. The data used in this study consist ofprimary data and secondary data both qualitative and quantitative in relation tothe stock of paper raw materials. Primary data obtained through observation aswell as direct interviews with various parties concerned. Secondary data isobtained from company management documents and reports. The results of thisstudy indicate that the application of EOQ (Economic Order Quantity) methodon UD. Sagga Leather Malang is more efficient than the simple method used bythe company. The application of this method does emphasize how important theraw material inventory planning for the company in the production process.Keywords: Economical order quantity (EOQ), Inventory.